Phenolic Compounds and Antioxidant Properties of Thai rice Paddy Herb as Affected by Different Drying Temperature - Wanyo, P.; Huaisan, K.; Chamsai, T. (International Journal of Agricultural Technology, 2018)
The present study investigated the changes in color and the contents and compositions of bioactive compounds in rice paddy herbs as affected by air-drying with different temperature. Phenolic compounds and their antioxidant activities of L. aromatica and L. geoffrayi dried by hot-air (HA) oven and vacuum (VC) oven at different temperatures (50, 60, 70, and 80 °C) were evaluated. Overall, changes in the color value (ΔE) were increased with increasing of HA drying temperature, while the increasing temperature of VC drying method led to ΔE decreased. Rice paddy herbs dried with VC drying method had higher contents of 2,2-diphenyl-1-picrylhydrazyl radical scavenging activities, ferric-reducing antioxidant power, total antioxidant capacity, total phenolic content (TPC) and total flavonoid content (TFC), compared with those dried with HA drying method. The TPC and TFC of samples dried by VC, the contents were increased when the drying temperature was increased from 50 to 70 °C but decreased at 80 °C. The most predominant phenolic was sinapic acid for all samples dried with temperature of 50-80 °C extract, ranged from 30-50 and 34-53 mg/g in HA dried L. aromatica and L. geoffrayi, respectively, and the VC dried L. aromatica and L. geoffrayi were 41-53 and 44-55 mg/g, respectively. Our results have demonstrated that VC drying at 70 oC should be considered as suitable drying method for rice paddy herbs with respect to preserving its color, antioxidant properties, and phenolic compounds.